2018
DOI: 10.3171/2018.4.focusvid.17721
|View full text |Cite
|
Sign up to set email alerts
|

Anterior two-thirds corpus callosotomy via stereotactic laser ablation

Abstract: Anterior two-thirds corpus callosotomy is a common palliative surgical intervention most commonly employed in patients with atonic or drop seizures. Recently, stereotactic laser ablation of the corpus callosum without a craniotomy has shown promise in achieving similar outcomes with fewer side effects and shorter hospitalizations. The authors demonstrate ablation of the anterior two-thirds corpus callosum in a patient with Lennox-Gastaut syndrome and drug-resistant drop seizures. Technical nuances of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…We performed the catheter placement in a similar fashion to that of Karsy et al, as recently published. 12 A stab incision was made in the scalp and the laser probe was introduced stereotactically and secured by a guidance bolt used to direct the laser probe. In cases 1 and 2 an additional incision was made for a second laser trajectory in order to allow ablation of the intended portions of the corpus callosum.…”
Section: Operative Techniquementioning
confidence: 99%
“…We performed the catheter placement in a similar fashion to that of Karsy et al, as recently published. 12 A stab incision was made in the scalp and the laser probe was introduced stereotactically and secured by a guidance bolt used to direct the laser probe. In cases 1 and 2 an additional incision was made for a second laser trajectory in order to allow ablation of the intended portions of the corpus callosum.…”
Section: Operative Techniquementioning
confidence: 99%
“…Its advantages have also been translated to the management of pediatric pathologies, such as in the successful reduction of seizure burden in the treatment of pediatric epilepsy for etiologies including focal cortical dysplasia, 3 mesial temporal lobe sclerosis, 14 and hypothalamic hamartoma, 27 among others (Table 1). 12,13 Kuo et al demonstrated successful reduction in tumor volume and associated symptoms in patients with gangliogliomas, radiation necrosis, focal cortical dysplasia, and gliosis. 13 Jethwa et al reported a supratentorial primitive neuroectodermal tumor (PNET) treated with LITT in which there was resolution of neurological symptoms and no evidence of definitive recurrence at the 6-month follow-up.…”
mentioning
confidence: 99%
“…This patient had no further episodes of atonic seizures and a > 50% reduction in overall seizure frequency at the 4-month follow-up. In 2018, Karsy et al [10] described an anterior two-thirds callosotomy using minimally invasive laser ablation, with an immediate and significant reduction in the number and severity of symptoms, fewer emergency room visits, and no surgical complications at the 9-month follow-up. These cases and ours suggest that laser callosotomy may be a safe and effective alternative to open corpus callosotomy, and also provides greater comfort and a faster recovery without compromising efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…We used 2 trajectories to achieve an anterior corpus callosotomy. Karsy et al [10] described using 3 trajectories to achieve anterior corpus callosotomy in a patient with Lennox-Gastaut syndrome and drug-resistant drop seizures. Another study described using a single trajectory for an anterior two-thirds corpus callosotomy and 2 trajectories for complete callosotomy [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation